2017
DOI: 10.1111/age.12532
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a distal chromosome 4 QTL affecting growth and muscle mass in a chicken advanced intercross line

Abstract: In our previous research, QTL analysis in an F cross between the inbred New Hampshire (NHI) and White Leghorn (WL77) lines revealed a growth QTL in the distal part of chromosome 4. To physically reduce the chromosomal interval and the number of potential candidate genes, we performed fine mapping using individuals of generations F , F and F in an advanced intercross line that had been established from the initial F mapping population. Using nine single nucleotide polymorphism (SNP) markers within the QTL regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In a previous study, we found a highly significant QTL (3.4 Mb, from 73 629 630 to 77 032 597 bp) on chicken chromosome (GGA) 4 affecting growth in an advanced intercross population (AIL) produced from an initial cross between an inbred New Hampshire line (NHI) and White Leghorn (WL77) line (Lyu et al . ). In the current study, a purebred high‐performing white layer line (WLA) with White Leghorn origin was used (Lieboldt et al .…”
Section: Association Analysis Between Snps Within the Previous Detectmentioning
confidence: 97%
See 2 more Smart Citations
“…In a previous study, we found a highly significant QTL (3.4 Mb, from 73 629 630 to 77 032 597 bp) on chicken chromosome (GGA) 4 affecting growth in an advanced intercross population (AIL) produced from an initial cross between an inbred New Hampshire line (NHI) and White Leghorn (WL77) line (Lyu et al . ). In the current study, a purebred high‐performing white layer line (WLA) with White Leghorn origin was used (Lieboldt et al .…”
Section: Association Analysis Between Snps Within the Previous Detectmentioning
confidence: 97%
“…To better overlay the results of the current results in WLA population with the previous study in the NHI × WL77 AIL, the top marker in the AIL study—rs314961352 at 75 451 915 bp on GGA4—was genotyped in the WLA population using allele‐specific PCR, as described previously (Lyu et al . ). Analysis of genotypes for this marker in relation to growth traits further confirmed the significant effect on daily weight gain from 8 to 14 weeks in the WLA population (LOD = 5.71; Table ).…”
Section: Association Analysis Between Snps Within the Previous Detectmentioning
confidence: 97%
See 1 more Smart Citation
“…Genotyping and sequencing: Genome-wide linkage analysis using 123 microsatellite (short sequence repeats; SSR) and single nucleotide polymorphism (SNP) loci were sued to map QTL covering 25 chromosomes (for detail see Goraga et al 2012;Nassar et al 2012Nassar et al , 2015. Chicken 60K and 600K SNP chips as well as whole genome sequencing were used to fine map and characterize the major growth QTL in the distal part of chromosome 4 (for detail see Lyu et al 2017).…”
Section: Materials and Strategiesmentioning
confidence: 99%
“…Pairwise tests of LD were performed for used markers in every generation using the SHESIS software platform (http://analysis.biox.cn/myAnalysis.php). We used the LME4 package in R (version 3.1.3) to perform the association analysis between genotypes and growth or body composition traits (see Lyu et al 2017 for detail).…”
Section: Materials and Strategiesmentioning
confidence: 99%